Is more information better? The role of consumers’ perception of water bills to promote consumption adaptation to climate change - Monteiro, H.; Rita Martins; Patrícia Moura e Sá; Emanuel-Correia, R. (ACC2016 - International Conference on Adapting to Climate Change: water, waste and other local infrastructure, 2016)
The mitigation approach is failing the goal of curbing CO2 emissions, urging the need to focus on adaptation policies to prevent global warming and its potentially extreme impacts, namely on water resources availability. Promoting a parsimonious use of this resource by consumers requires a more effective communication strategy by utilities and regulators. The water invoices are expected to be useful tools in managing water resources if they are able to convey adequate information to consumers. We look at the question of whether more information is better to promote consumers’ understanding of their bills. The main purpose of this paper is to uncover the factors affecting consumers’ perception of their water bills. To achieve this goal, a survey questionnaire was administered to over two thousand Portuguese residential users and data from utilities was collected. Results show that consumers’ perceptions of water charges significantly differ from actual levels. Empirical findings also reveal that higher consumption levels and subscribing to electronic invoices positively influence such discrepancy, while perceived price fairness and a clear and separate indication of the amount billed are correlated with a more accurate perception of the amount billed.